Konsep Manajemen Mutu Pendidikan - Niken Ristianah; Toha Ma’sum (TABYIN: JURNAL PENDIDIKAN ISLAM, 2022)
Quality is the most important aspect in every educational institution, where quqlity is believed to be the main capital in facing competition. Therefore, managing and educational institution must be comprehensive and integrated. This is inseparable from how a institution manages that quality. Manajement of quality management is basically directed to meet consumer needs consistenly and achieve continous improvement in every aspect ot the activities of educational institution. Basically, quality management seeks to improve the quality of work productivity andefficiency trough performance improvement both internally and externally. The quality of education can be seen from the fulfillment of eight educational standart that must be met by school. The eight educational standart include, content standart (curriculum implementation and development), process standart, assessment standart, graduate competency standart, standart of educators and education personnel, standart of elemet management in educational institution, standart of education financing, standart of educational facilities and infrastructure.